Phosphorized SnO2/graphene heterostructures for highly reversible lithium-ion storage with enhanced pseudocapacitance. Issue 8 (2nd February 2018) - Yang, Ying; Zhao, Xu; Wang, Hong-En; Li, Malin; Hao, Ce; Ji, Min; Ren, Suzhen; Cao, Guozhong
Abstract : Phosphorized SnO2 /graphene nanocomposite was designed and synthesized for superior Li-ion storage properties due to the synergistic effect of multiple components. Abstract : Tin dioxide (SnO2 ) based materials are attractive anode candidates for lithium-ion batteries (LIBs) due to their high capacity, low cost and environmental friendliness. However, their practical applications have been hindered by their poor reversibility, sluggish reaction kinetics and huge volume expansion. This work demonstrates the facile synthesis of a partially phosphorized SnO2 /graphene nanocomposite (P-SnO2 @G) by a combined hydrothermal and low-temperature phosphorization process. Enhanced Li-ion storage performance has been achieved in such a nanocomposite due to the unique phase hybridization of crystalline SnO2, SnP x and metallic Sn homogeneously anchored on graphene nanosheets. The P-SnO2 @G composite also manifests a high initial coulombic efficiency of 79% and delivers a high and reversible capacity of 860 mA h g −1 at 0.5 A g −1 with 94% capacity retention after 50 cycles. In addition, P-SnO2 @G exhibits an excellent rate capacity of 736 mA h g −1 at 2.0 A g −1 . The greatly enhanced Li-ion storage capability stems from the significant pseudocapacitance contribution accounting for ∼82% at 1 mV s −1 . These results demonstrate that as-synthesized P-SnO2 @G composite is a promising anode material for LIBs. The proposed phase hybridization concept can pave the way for designing and exploring more advanced electrode materials for beyond Li-ion batteries.